Microdebrider and Complications in Endoscopic Surgery for Nasal Polyposis - Semih Sütay (Turkish Archives of Otorhinolaryngology, 2002)

(untitled)
Endoscopic sinus surgery (ESS) has become a standart therapy for chronic sinusitis. Since the introduction of powered instruments for ESS, an easier and faster way of resecting polyps was established. In this study complications of ESS for nasal polyposis operated with microdebrider on 100 sides of 51 patients were examined. There were no major complications. There were 1 (1%) orbital fat herniation, 2 (2%) anterior ethmoid artery traumas, 2 (2%) sphenopalatine artery traumas, 1 (1%) diffuse bleeding hampering the operation, 2 (2%) synechias between lateral wall and middle turbinate. Stenosis of the maxillary sinus ostia was detected on 5 sides (5%) of 3 patients. It is concluded that with its lower incidence of complications even in high risk cases such as nasal polyposis, microdebrider provides safety and ease in endoscopic sinus surgery.